Project financing evaluation for acquisition of floating storage and offloading facility - Priyokusumo, Andhika; Tjendrasa, Kin (The Indonesian Journal of Business Administration, 2016)
Abstract - The weakening of Crude Oil price has increasing the demand of Floating Storage and Offloading facility to store the Crude Oil while waiting the price go back increase. The demand also comes from oil producer company PT. Cahaya Pasifik Internasional (CPI), for the usage of floating storage in Corridor block, Bangka, Indonesia. PT. Bahtera Unggul Lestari (BUL), as one of the Indonesian shipping company would like to participate in the Floating Storage and Offloading. But due to negative Net Income and decreasing Retained Earnings in 2014, it is a challenge for BUL to provide the funding to purchase a Suezmax tanker and convert it to be Floating Storage and Offloading facility. Leasing or Bareboat Charter is not an option since the vessel ownership structure should be majority under Indonesian company and vessel are not allowed the have hardware structural change especially for Floating Storage and Offloading conversion. Another financing alternative is by establishing a Special Purpose Vehicle company under project finance method. Under project finance system, the SPV company will responsible for all project requirement, including sourcing the funding. The SPV company has separate legal incorporation and separate project Financial Statement apart from BULâ€™s corporate management. As Project Sponsor, BUL can only support with low amount equity due to limited working capital, and hence BUL targeting DSCR only 1.26x from average DSCR 1.5x. Using basic assumption with $54mio CAPEX, 92.39% gearing, 9% interest rate and Hire Rate $43,500/day, it resulting evaluation of 1.01x DSCR. Based on scenario planning, the most optimum condition is when the Project Manager able to reduce the CAPEX to be $49mio, and negotiating the interest rate to be 6%. This resulting good result with 1.87x DSCR bigger than target 1.26x, and positive NPV not only for firm and debt holder, but also for equity holder. Second alternative solution is by increasing daily Hire Rate to be $53,474/day, with the risk of losing the tender to other more competitive competitor.Â Keywords: Floating Storage and Offloading, project finance, Debt Service Coverage Ratio, gearing, scenario planning, hire rate, Special Purpose Vehicle, Suezmax, Bareboat Charter